1974
DOI: 10.1084/jem.140.3.718
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Cytotoxic T Lymphocytes in Vitro

Abstract: Mouse cytotoxic T lymphocytes (CTL) were generated in unidirectional mixed leukocyte cultures (MLC) using normal C57BL/6 spleen cells as responding cells and irradiated DBA/2 spleen cells as stimulating cells. Cytotoxicity was assayed on 51Cr-labeled P-815 (DBA/2) target cells, and the relative frequency of CTL in individual cell populations was estimated from dose-response curves. Upon inclusion of 2-mercaptoethanol in the culture medium, it was found that significant CTL activity could be detected for as lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(22 citation statements)
references
References 11 publications
(15 reference statements)
0
22
0
Order By: Relevance
“…After a 4-day stimulation period with low-dose IL-2 (100 IU/ml; Chiron) plus 2 mg/ml Hsp70 peptide TKD (aa [450][451][452][453][454][455][456][457][458][459][460][461][462][463] ; TKDNNLLGRFELSG), the cytolytic response was tested against Hsp70 high-expressing CX þ , Colo þ , and HeLa Bag-4 and low-expressing CXÀ, ColoÀ, and HeLa neo cells, either untreated or following irradiation (1 Â 10 Gy) and a recovery period of 24 h, in a standard [ 51 Cr] assay. 54 Briefly, different dilutions of effector and target cells (40 : 1 to 2 : 1) were coincubated in duplicates for 4 h at 371C, in a final volume of 200 ml. Then, supernatants (30 ml) were collected and radioactivity was measured on a g-counter (Topcount, Packard instrument).…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…After a 4-day stimulation period with low-dose IL-2 (100 IU/ml; Chiron) plus 2 mg/ml Hsp70 peptide TKD (aa [450][451][452][453][454][455][456][457][458][459][460][461][462][463] ; TKDNNLLGRFELSG), the cytolytic response was tested against Hsp70 high-expressing CX þ , Colo þ , and HeLa Bag-4 and low-expressing CXÀ, ColoÀ, and HeLa neo cells, either untreated or following irradiation (1 Â 10 Gy) and a recovery period of 24 h, in a standard [ 51 Cr] assay. 54 Briefly, different dilutions of effector and target cells (40 : 1 to 2 : 1) were coincubated in duplicates for 4 h at 371C, in a final volume of 200 ml. Then, supernatants (30 ml) were collected and radioactivity was measured on a g-counter (Topcount, Packard instrument).…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…During the course of tumor allograft rejection in mice, the distribution in sedimentation velocity of splenic CTL changes with time, suggesting that a transition from large to small CTL may occur (7)(8)(9). Since CTL could be detected for several weeks in MLC under appropriate culture conditions (13), it was of interest to investigate the physical properties of CTL induced in vitro. For this purpose, multiple cultures of 25 x 10 ~ C57BL/6 spleen cells and 25 × 10 e irradiated DBA/2 spleen cells were established.…”
Section: Methodsmentioning
confidence: 99%
“…Since a rapid appearance of high levels of CTL activity could be demonstrated following secondary antigenic stimulation in long-term MLC (13), it was of considerable interest to investigate whether residual CTL were responsible for this activity. To this end, day 14 MLC cells were separated by velocity sedimentation at unit gravity and divided into three pooled fractions corresponding to those described in the previous section.…”
Section: Characterization Of Cells Responsive To Secondary Alloantigementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, either there was no reciprocal cell death, or the a effector cells greatly exceeded the d effector cells. Although there is, as yet, no reliable indicator of the absolute number of effector cells present in a lytically active cell population, it is a common practice to consider that populations with comparable levels of cytolysis have a similar incidence of effector cells (10). As the cytolytic activity of the a anti-d and d anti-b cell populations towards homologous tumor target cells was comparable in the studies reported here, we assume that the effector cell incidence in the attacking and target populations did not markedly differ.…”
Section: B10a Spleen Cells Sensitized To B10d2 Cells (A Anti-d Cellmentioning
confidence: 99%